ChemInform Abstract: Synthesis of C6‐Pyridylpurine Nucleosides by Reaction of Nebularine N1‐Oxide with Pyridinyl Grignard Reagents. Issue 31 (August 2015) - D'Errico, Stefano; Oliviero, Giorgia; Borbone, Nicola; Nici, Fabrizia; Piccialli, Vincenzo; Pinto, Brunella; D'Alonzo, Daniele; Mayol, Luciano; Piccialli, Gennaro
Abstract The synthesis of the title compounds in moderate to good yields is reported.